Environmental education for the younger generation at the Taman Keanekaragam Hayati Subang - Prasetyo Nugroho; Rany Juliani; Apriliyanti Dwi Rahayu; Indarto Indarto; Nida Ankhoviyya; Alfian Dwi Cahyo (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2022)
The integration of learning activities in schools and environmental education is considered capable of increasing students’ knowledge, understanding, and positive behavior towards the environment. The aim of the environmental education program at Taman Kehati Subang was to investigate its role in supporting environmental education activities of the students of SMK Tri Surya Bangsa, Subang. It was conducted on August 21, 2020 and was attended by 10 representatives’ students of class X, XI, and XII and 2 accompanying teachers. Outdoor activities, games, and field practice were used to deliver the material. It includes organic cultivation, biodiversity conservation, nurseries and compost making, cipondoh water sources, and soil and water conservation. Our evaluation showed that students hold high agreement that Taman Kehati has various types of plants and suitable to support environmental education activities in schools. Students assessed that a visit to Taman Kehati provided new experiences that could increase their knowledge of environmentally natural resource management. Delivering material with a combination of outdoor activities, field practice, and games makes them easy to be understood and can be practiced daily. It can be concluded that students and teachers generally consider that Taman Kehati is suitable to support the integration of learning in schools and environmental education. Students were very satisfied with the environmental education activities at Taman Kehati, Subang